The McGraw-Hill handbook - Maimon, Elaine P.; Peritz, Janice H.; Yancey, Kathleen Blake , 1950- (McGraw-Hill Higher Education, 2010)
A handbook for achieving excellence in the ever-changing digital environment that students confront in college